The impulse of force as an effective indicator of exercise capacity in competitive rowers and canoeists - Domaszewska, K.; Krysciak, J.; Podgórski, T.; Nowak, A.; Ogurkowska, M. (Journal of Human Kinetics, 2021)
The aim of the research was to present the importance of measuring the impulse of force in assessing exercise capacity in professional rowers and canoeists rather than conducting traditional physiological and biochemical analyses. A group of 20 athletes (12 rowers and 8 canoeists) underwent progressive intensity exercise tests in two testing sessions (before and after a training period). During the tests, maximal aerobic capacity, impulse of strength, metabolic indices, and markers of skeletal muscle damage were assessed. Total testosterone, free testosterone, cortisol, interleukin 1,6, and creatine kinase were evaluated in venous blood. The impulse of force at the ventilatory threshold and at the maximum load was correlated with free testosterone and a total testosterone/cortisol ratio during exercise (p = 0.05) and was negatively correlated with cortisol concentration (p = 0.05) in the first testing session (before training intervention). Values were positively correlated with concentration of total testosterone, free testosterone and total testosterone/cortisol, and free testosterone/cortisol ratios during exercise (p = 0.05) in the second testing session (after training intervention). Biochemical indices of overtraining were correlated with maximum oxygen uptake in each session and with the impulse of force at the ventilatory threshold and the maximum load of exercise. Thus, there is an indirect relationship between maximal aerobic capacity and the impulse of force. The measurement of the impulse of force can become a simple and effective method for evaluating the overall exercise capacity of rowers because of its relationship with indices of the load and changes in hormonal indices of anabolic and catabolic processes during exercise. Therefore, it may constitute a replacement for the traditional laboratory measurement of VO 2max in highly qualified rowers and canoeists.